2010
DOI: 10.1155/2010/828249
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Corrosion Inhibition of Mild Steel Using Piper Nigrum L. in Different Acid Medium

Abstract: The inhibition of corrosion of mild steel usingPiper nigrumL in different acid medium by weight loss method was investigated. The corrosion inhibition was studied in hydrochloric acid and sulphuric acid by weight loss method at different time interval at room temperature. The result showed that the corrosion inhibition efficiency of this compound was found to vary with different time interval and different acid concentration. Also, it was found that the corrosion inhibition behavior ofPiper nigrumL is greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The thin layer of the oxides adhered to the metal surface, resulting in a decrease in the corrosion rate. Similar results have been reported by [14,16]. …”
Section: Determination Of Phytoconstituents Of the Gvsupporting
confidence: 92%
“…The thin layer of the oxides adhered to the metal surface, resulting in a decrease in the corrosion rate. Similar results have been reported by [14,16]. …”
Section: Determination Of Phytoconstituents Of the Gvsupporting
confidence: 92%
“…In addition to the bands in the 850-1061 cm À 1 range, the band due to the stretching of Ce-O is found at 700 cm À 1 . The XRD pattern of the sample exhibits the characteristic peak at 2y ¼28.41, which corresponds to the (111) plane [6]. It also exhibits the planes such as (200), (220), (311), (222), (400) and (331) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The author concluded that the packed orange juice with preservatives was most corrosive followed by natural orange juice and water respectively. The inhibition of corrosion of mild steel using piper nigrum L in different acid medium was investigated by Anand and Balasubramanian (2010). The authors studied the corrosion resistance of this mild steel in hydrochloric and sulphuric acid by weight loss method at different time interval at room temperature.…”
Section: Introductionmentioning
confidence: 99%